Spectral Telepathy: the Late Style of Susan Howe - Marjorie Perloff (Transatlantica)
Susan Howe’s late style marks a departure from her earlier work. Two books recently published—The Quarry (New Directions, 2015) and Tom Tit Tot (Museum of Modern Art, 2015) illustrate this point. Whereas Howe’s earlier books of critical prose—for example, My Emily Dickinson (1985)—used scholarship to buttress Howe’s critical positions and arguments, her new “essays” in The Quarry are more properly understood as poems. When we analyze Howe’s meditations on Wallace Stevens, we learn that she identifies with Stevens to create a new poetic hybrid. And the language and rhythm of these new essays is that of a poetic construct. In the same vein, her long poetic sequence, Tom Tit Tot, made up of fragments of other people’s writings, the underlying thread being the fairy tale of Rumpelstiltskin (Tom Tit Tot), is a conceptual work that appropriates fragments of other texts so as to create an entirely new angle on the fairy tale and its cognates. Both of these new books show how contemporary technique—facsimile, xerography, overprint, digital processing—can reanimate literary texts and make them new. Howe’s austere later writing is perhaps her very finest.